A THEORETICAL EVALUATION OF CONSERVATION PROBLEMATIQUE: COMPARISON OF INSTITUTIONAL SITE MANAGEMENT) AND PLURALIST (ACTOR NETWORK THEORY) APPROACHES - Secilmisler, Tore; Yenen, Zekiye (YILDIZ TECHNICAL UNIV, 2011)
Since the last quarter of the 20th century, humankind lives the information revolution which is based on developments in information technology. This change in technology also have caused changes in communities. In this context, paradigm shift has occured in social life. During this shift community which has modern values starts to have postmodern values. The process of the paradigm shift in social life, changed the perspective of the planning, the government approach and the cultural heritage. At the present time the main reason of the loss of cultural heritage issue is explained in the sense of actor network actions which exist during the reproduction of urban spatial process, with the idea of generating revenue from urban land. From this point, this study aims to examine the relationship between the problem of the loss of heritage and social relations which exist during the reproduction and use of urban land process in the context of paradigm shift and expressed as actor network. In this direction, this study's theoretical framework is formed in the context of relation between social processes and physical space, paradigm shift between modern and postmodern eras. In this study, 'site management' structure which is based on institutionalism and 'actor network theory' are comparatively evaluated.
Keywords: Actor network theory; community and paradigm shift; cultural heritage; institutional approach; site management; Engineering